2015
DOI: 10.1103/physrevb.91.064409
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing and increasing the magnetic moment of half-metals: The role of Li in half-HeuslerLiMnZ(Z=N,P,Si)

Abstract: Li-based half-Heusler alloys have attracted much attention due to their potential applications in optoelectronics and because they carry the possibility of exhibiting large magnetic moments for spintronic applications. Due to their similarities to metastable zinc blende half-metals, the halfHeusler alloys β-LiMnZ (Z = N, P and Si) were systematically examined for their electric, magnetic and stability properties at optimized lattice constants and strained lattice constants that exhibit half-metallic properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…If Z is a group IV element, then the moment is 4 µ B per Mn. 8 However, the lattice constants are consistently larger than the optimized values. This may be caused by the fact that the pnictides and Si do not have a sufficiently strong enough electronegativity.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…If Z is a group IV element, then the moment is 4 µ B per Mn. 8 However, the lattice constants are consistently larger than the optimized values. This may be caused by the fact that the pnictides and Si do not have a sufficiently strong enough electronegativity.…”
mentioning
confidence: 87%
“…For example, Damewood et al examined half-metallic properties and stability of lithiated half-Heusler alloys, LiMnZ (Z=N, P, Si). 8 They found that the studied alloy exhibit half-metallic properties at lattice constants larger than its' optimized lattice constant. In fact, many zinc-blende (ZB) compounds, such as MnZ, are not half-metallic at their equilibrium lattice constants but can also a To whom correspondence should be addressed.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Then, quite a lot of half-Heusler alloys [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] had been predicted to be HM materials (HMMs). Recently, the electronic, magnetic, and stability properties were systematically investigated by first principles calculation in half-Heusler alloys of LiMnZ (Z = N, P, Si) [ 16 ]. Damewood et al found that these LiMnZ (Z = N, P, Si) alloys show HM behaviors with large semiconducting-type band-gaps and magnetic moments (>3 μ B per formula unit) at their strained lattice constants.…”
Section: Introductionmentioning
confidence: 99%
“…The Heusler alloys generally have two variants of stoichiometric compositions: the half-Heusler compound with generic formula of XYZ [52][53][54][55][56][57] and the full Heusler compound X 2 YZ [5,58,59], where X and Y are from transition metal elements and Z from main group elements. In both half and full Heusler alloys, they normally crystalize in a cubic structure yet with different configurations [60]: non-centrosymmetric cubic structure C1 b for half-Heusler; two different types for full Heusler: the Cu 2 MnAl structure with space group Fm3m, also known as L2 1 -type, and the Hg 2 CuTi structure with space ground F43m, also known as "inverse structure" or XA-type.…”
Section: Crystal Structure and Equilibrium Latticementioning
confidence: 99%